New constraints on direct collapse black hole formation in the early Universe - Agarwal, Bhaskar; Smith, Britton; Glover, Simon; Natarajan, Priyamvada; Khochfar, Sadegh (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. Direct collapse black holes (DCBH) have been proposed as a solution to the challenge of assembling supermassive black holes by z > 6 to explain th
Gesehen am 11.08.2020